Omega-3 Docosahexaenoic Acid (DHA) Impedes Silica-Induced Macrophage Corpse Accumulation by Attenuating Cell Death and Potentiating Efferocytosis - Rajasinghe, Lichchavi D.; Chauhan, Preeti S.; Wierenga, Kathryn A.; Evered, Augustus O.; Harris, Shamya N.; Bates, Melissa A.; Gavrilin, Mikhail A.; Pestka, James J. (Frontiers in Immunology, 2020)
Airway exposure of lupus-prone NZBWF1 mice to crystalline silica (cSiO2), a known trigger of human autoimmune disease, elicits sterile inflammation and alveolar macrophage death in the lung that, in turn, induces early autoimmune onset and accelerates lupus progression to fatal glomerulonephritis. Dietary supplementation with docosahexaenoic acid (DHA), a marine ω-3 polyunsaturated fatty acid (PUFA), markedly ameliorates cSiO2-triggered pulmonary, systemic, and renal manifestations of lupus. Here, we tested the hypothesis that DHA influences both cSiO2-induced death and efferocytotic clearance of resultant cell corpses using three murine macrophage models: i) primary alveolar macrophages (AM) isolated from NZBWF1 mice; ii) self-renewing AM-like Max Planck Institute (MPI) cells isolated from fetuses of C57BL/6 mice, and iii) RAW 264.7 murine macrophages, a virus-transformed cell line derived from BALB/c mice stably transfected with the inflammasome adaptor protein ASC (RAW-ASC). Incubation with cSiO2 at 25 and 50 g/ml for 6 h was found to dose-dependently induce cell death (p<0.05) in all three models as determined by both acridine orange/propidium iodide staining and release of lactate dehydrogenase into cell culture supernatant. Preincubation with DHA at a physiologically relevant concentration (25 μM), significantly reduced cSiO2-induced death (p<0.05) in all three models. cSiO2-induced cell death and its suppression by DHA were associated with caspase 3/7 activation, indicative of apoptosis, in AM, MPI, and RAW-ASC cells and with caspase-1 activation, suggestive of pyroptosis, in MPI cells. Fluorescence microscopy revealed that all three macrophage models were similarly capable of efferocytosing RAW-ASC target cell corpses. Furthermore, MPI effector cells could likewise engulf RAW-ASC target cell corpses elicited by treatment with staurosporine (apoptosis), LPS and nigericin (pyroptosis), or cSiO2. Preincubation of RAW-ASC target cells with 25 μM DHA prior to death induced by these agents significantly enhanced their efferocytosis (p<0.05) by MPI effector cells. In contrast, pre-incubating MPI effector cells with DHA did not affect engulfment of RAW-ASC target cells preincubated with vehicle. Taken together, these findings indicate that DHA at a physiologically relevant concentration was capable of attenuating macrophage death and could potentiate efferocytosis, with the net effect of reducing accumulation of cell corpses capable of eliciting autoimmunity.